Pengaruh Penggunaan Informasi Akuntansi Terhadap Keberhasilan Usaha Mikro Kecil Menengah (Studi Pada UMKM di Kecamatan Alok Kabupaten Sikka) - Emanuel Darwis Yoseph Mite; Maria Nona Dince; Paulus Libu Lamawitak (Jurnal Riset Akuntansi, 2023)
This study aims to determine the effect of using accounting information on the success of micro, small and medium enterprises in Alok District, Sikka Regency. The method used in this study is a quantitative method with primary data sources in the form of questionnaires which were distributed to MSME actors in Alok District with a total of 30 respondents. The analytical method in this study is the research instrument test, classical assumption test, simple regression analysis and hypothesis testing. The results obtained in this study show that the use of accounting information influences the success of micro, small and medium enterprises in Alok District, Sikka Regency. This shows that the use of good and accurate accounting information will have a positive impact on the success of a business.